Evaluation of the solid-phase competition ELISA for detecting SAT foot-and-mouth disease virus vaccination and infection in goats - Fosgate, Geoffrey Theodore (University of Pretoria, 2024)
Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2021.